A Study of Classroom Inquiry and Reflection Among Preservice Teachers Candidates - Duquette, Cheryll; Dabrowski, Leah (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2016)
The purpose of this study was to explore the experiences of four preservice teachers who used classroom inquiry and reflection to solve problems when implementing differentiated instruction in elementary classrooms during a practicum. Data from classroom observations, individual reflections, and discussions with a teacher educator were analyzed inductively. The findings show that the preservice teachers were able to describe their situations and reflect individually and collaboratively to analyze and resolve problems related to instruction, discipline, and student learning. The results extend our understanding of how teacher educators, mentors, or instructional coaches may provide preservice teachers with individualized support that can facilitate inquiry and reflection during their practica.